Sex comparism of white Fulani cattle blood profile in Southwestern Nigeria (2013)
Sexual dimorphism has been established in the brain regions of farm animals and poultry, but for their blood, reports do not agree as to differences at the same age. While some reports show no differences except for pregnant and lactating females, others indicate Otherwise. This study was carried out to investigate the blood of white Fulani breed of cattle in southwestern Nigeria if there could be differences at same mature age (4yr). A total of 100 cattle were used consisting of 50 bulls and 50 cows. Full haematology was investigated using the Vet AutoHaemoanalyser machine. Some serum metabolites were also investigated including total Protein, Albumin and total cholesterol. Data obtained were subjected to one-way analysis of variance (ANOVA). The results show that white blood cell count (WBC) was significantly (P<0.05) higher in females (17.23±1.08) than in males (12.25±0.77). Mean Corpuscular haemoglobin concentration (MCHC) also showed sex differences with females having higher and significant (P<0.05) average value (33.8±0.19) than males (32.6±0.24). The results from Serum analysis show that bulls (with 37.8±0.54) have higher and significant (P<0.05) Albumin values than cows (34.9±0.29). Though the results obtained in this study fall within normal ranges for this species, it however does not indicate any specific sex effect for this breed.